Niger - Joint World Bank-IMF Debt Sustainability Analysis - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
Niger's risk of external and overall public debt distress is rated "moderate" as in the previous DSA. While all thresholds are observed in the baseline, the PV of PPG external debt-to-exports ratio breaches its threshold under stress test scenarios. Debt-carrying capacity continues to be rated "medium." The analysis shows that Niger has limited space to accommodate negative shocks and remains vulnerable to adverse developments of its exports. The DSA is predicated on the government continuing to implement its reform program: fiscal consolidation; structural reforms, including revenue mobilization efforts; contain expenditures and improve spending quality; and timely completion of several large-scale projects, in particular the construction of a pipeline for crude oil exports. Identified weaknesses call for further strengthening of debt management, including by broadening the coverage of public debt, prioritizing concessional borrowing, and strengthening private-sector development to support economic diversification and mitigate the risks associated with commodity price fluctuations.